Legal analysis of river pollution control and prevention in Kurdistan Iraq - Ali, Hiwa Rashid (2024)
Rivers are the main source of potable water, as a human right, and have socioeconomic value for the whole society. Among the main factors of river pollution are industrialization, population growth, and the effects of climate change. For instance, the Tanjero River in Kurdistan, Iraq, is seriously polluted due to a lack of legal framework and poor water management. Thus, the key objective of this study is to critically analyze the legal framework and water management in Kurdistan to curb the problem of river pollution. The study adopts doctrinal, socio-legal, and qualitative approaches to analyze the primary and secondary data. In the case of the Tanjero River, the main legal frameworks analyzed include Law No. 8 (2008) for Environmental Protection and Improvement, Law No. 3 (2010) for Environmental Protection and Improvement Board, and Law No. 4 (2022) for Water Management and Protection in the Kurdistan region of Iraq. This study found that, although the international legal instruments provided a general guideline on water protection and sustainable water management, enforcement is still lacking because of the absence of a binding international law concerning river protection. Moreover, in Kurdistan, the existing legal provisions on river protection are inadequate due to an incomprehensive legal framework, poor enforcement of protective legal mechanisms, institutional fragmentation, and poor coordination among governmental institutions. Thus, some of the provisions in Law No. 8 (2008) for Environmental Protection and Improvement, Law No. 3 (2010) for Environmental Protection and Improvement Board, and Law No. 4 (2022) for Water Management and Protection in the Kurdistan region of Iraq need to be amended to address the problem. An active integration system and good coordination between ministries in Kurdistan are crucial to sustainably establishing better water management. It is suggested that the power of the Environmental Board and Water Council (WCR) in Kurdistan be given to an independent body that will be able to tackle this problem more effectively. Also, better coordination between Hawler and Baghdad is necessary to face the current water challenges in the climate change era.